Modern Java collections (LiveLessons (Indianapolis, Ind.), 2018)
"Learn everything you need to know to get the most of the Java Collections Framework. Simon Roberts, best-selling Java author and trainer, will detail the nuances of working with collections, so you can better understand the concepts and see firsthand how to use this powerful API. This course is an essential guide to learning how the collections API--which is rich with functionality--can help with regular programing projects. In addition to learning about interfaces, classes, and methods, you will explore design questions, why the API is the way it is, and how you can use it for best effect. You will also learn how to break up complex coding problems and how to more efficiently maintain code. You will actually explore design patterns and principles used in the collections API that are applicable to many areas of programing. This course takes a different approach from most Java courses, using a story-like approach to teach concepts. Topics start by looking at a problem, considering how it might be solved, and steadily working to more advanced solutions, while building understanding of the concepts, libraries, and syntax being used. You will develop a thorough understanding of each chunk of knowledge, so you are ready to use that understanding in your daily coding. You will start by taking a look at generalization in collections and explore key collection API interfaces. You will then find out why there's a need for generics, see general tools you can use, and take a look at some use cases. After that you will dive in, exploring investigating lists, array-based implementations of a list, linked implementation, and more. The next step is then understanding iterating collections, equality, orders, hash codes, and hashed storage before jumping into sets, trees, improving designs, maps, implementing the iterator pattern, the new functional methods added with Java 8, and more interfaces. You will then take a look at list implementations and utilities for collections. The course will wrap things up with a section on creating and combining comparators, which includes more functional additions to the APIs."--Resource description page